Mesenchymal Stem Cells Shift Mitochondrial Dynamics and Enhance Oxidative Phosphorylation in Recipient Cells - Newell, Christopher; Sabouny, Rasha; Hittel, Dustin. S.; Shutt, Timothy E.; Khan, Aneal; Klein, Matthias S.; Shearer, Jane (Frontiers in Physiology, 2018)
Mesenchymal stem cells (MSC) are the most commonly used cells in tissue engineering and regenerative medicine. MSC can promote host tissue repair through several different mechanisms including donor cell engraftment, release of cell signaling factors and the transfer of healthy organelles to the host. In the present study, we examine the specific impacts of MSC on mitochondrial morphology and function in host tissues. Employing in vitro cell culture of inherited mitochondrial disease and an in vivo animal experimental model of low-grade inflammation (high fat feeding), we show human-derived MSC to alter mitochondrial function. MSC co-culture of skin fibroblasts from mitochondrial disease patients rescued aberrant mitochondrial morphology from a fission state to a more fused appearance indicating an effect of MSC co-culture on host cell mitochondrial network formation. In vivo experiments confirmed mitochondrial abundance and mitochondrial oxygen consumption rates were elevated in host tissues following MSC treatment. Furthermore, microarray profiling identified 226 genes with differential expression in the liver of animals treated with MSC, with cellular signaling and actin cytoskeleton regulation as key upregulated processes. Collectively, our data indicate that MSC therapy rescues impaired mitochondrial morphology, enhances host metabolic capacity and induces widespread host gene shifting. These results highlight the potential of MSC to modulate mitochondria in both inherited and pathological disease states.